Intervensi Token Economy Berbasis Dukungan Sosial Keluarga Pada Anak Kecanduan Game Online - Ulfa Dwi Asrianti; Bachtiar Safrudin; Kartika Setia Purdani; Burhanto Burhanto (Nan Tongga Health And Nursing, 2026)
Online game addiction in school-aged children causes community health problems that impact sleep pattern disturbances, decreased social interaction, and the emergence of ineffective coping communities due to violations of family supervision. This study aims to analyze the practice of community killing through the application of token economy based on family social support to reduce online game addiction in children aged 10–12 years. The study used a case study design with a community nursing process approach in five children with a playing duration of 5–8 hours per day before being given the intervention. Data were collected through behavioral observations, family interviews, and recording the duration of playing before and after the intervention. The intervention was carried out for six days through the application of token economy to reinforce desired behaviors and reduce undesirable behaviors with predetermined targets combined with play therapy and active family involvement. The results showed a decrease in playing duration from an average of eight hours to three hours per day, accompanied by improved sleep patterns and increased adaptive behavior that persisted after the intervention was stopped. It was concluded that family involvement in the behavioral reinforcement system through token economy is effective in forming more adaptive coping. This intervention is recommended for community nurses and needs to be developed in studies with larger samples and longer duration.